抗生素是否有助于降低治疗皮肤癌的皮肤外科手术后的创面感染风险?. (14th February 2018) - Chan, S.A.; Wernham, A.G.H.; Stembridge, N.; Harper, N.; Verykiou, S.; Fremlin, G.A.; Abbott, R.A.; Matin, R.N.
Abstract : Linked Article: Chan et al. Br J Dermatol 2018;178 :394–399